Quality Management Philosophy at Mts Laboratory UINSU Medan - Fachruddin Fachruddin; Sarah Lailatilfadla; Eka Lestari; Muhammad Irgi Maulana Nst (Educan : Jurnal Pendidikan Islam, 2023)
The purpose of this research is to find out the application of the philosophy of quality and the obstacles to its application in madrasah tsanawiyah. This research is a qualitative research (field research) with observations and searching for data directly to the location and objects studied at MTs LAB UINSU. The results of this study indicate that, 1) the application of the philosophy of quality management in MTs LAB UINSU, by referring to the vision and mission of the madrasah which is used as a guide in developing madrasah programs in the short, medium, and long term; 2) obstacles that occur in applying the quality management philosophy at MTs LAB UINSU are the lack of communication between the madrasah and students parents. This is due to parents not participating in the development of madrasah programs. Following up on this, the madrasah communicates only with students, only then students convey matters related to the madrasah program to the parents of students.